2022
DOI: 10.1007/s00394-022-02998-6
|View full text |Cite
|
Sign up to set email alerts
|

Whole fresh fruit intake and risk of incident diabetes in different glycemic stages: a nationwide prospective cohort investigation

Abstract: Purpose Fruit intake is beneficial to several chronic diseases, but controversial in diabetes. We aimed to investigate prospectively the associations of whole fresh fruit intake with risk of incident type 2 diabetes (T2D) in subjects with different glucose regulation capacities. Methods The present study included 79,922 non-diabetic participants aged ≥ 40 years from an ongoing nationwide prospective cohort in China. Baseline fruit intake information was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…1 and Supplementary Table S2 summarize the key findings. Some main findings were: 1) decreased risk of DM was associated with increased dietary intakes of coarse grain, 7 , 8 fresh fruit, 9 , 10 , 11 wheat, 11 and vegetables, 8 , 11 while there was an increased risk with higher intakes of total fat and carbohydrates, 12 fish, 13 red meat, 11 , 13 , 14 and junk food 8 ; 2) CVD risks were lower with higher intakes of peanuts, 15 unprocessed meats, 16 and total fiber 17 ; 3) lower cancer risks were associated with several dietary patterns (i.e., the Alternative Healthy Eating Index updated in 2010, 18 an alternate Mediterranean diet score, 18 Dietary Approaches to Stop Hypertension [DASH], 18 a high-dairy and high-fruit-and-vegetable and low-alcohol pattern score, 19 and vegetable-fruit-soy pattern 20 ), food groups (i.e., higher intakes of milk, 21 , 22 red meat, 23 , 24 , 25 vegetables, 26 , 27 and fruits, 26 , 28 as well as lower consumption of grilled meat, 29 high-cholesterol foods, 29 and processed meat intake 30 ), some nutrients (i.e., lower sodium, 31 , 32 and saturated fat 33 ); and 4) a higher risk of COPD was associated with lower fish intake 34 and in those with a smoking history. 35 Please see more results in Supplementary Table S2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and Supplementary Table S2 summarize the key findings. Some main findings were: 1) decreased risk of DM was associated with increased dietary intakes of coarse grain, 7 , 8 fresh fruit, 9 , 10 , 11 wheat, 11 and vegetables, 8 , 11 while there was an increased risk with higher intakes of total fat and carbohydrates, 12 fish, 13 red meat, 11 , 13 , 14 and junk food 8 ; 2) CVD risks were lower with higher intakes of peanuts, 15 unprocessed meats, 16 and total fiber 17 ; 3) lower cancer risks were associated with several dietary patterns (i.e., the Alternative Healthy Eating Index updated in 2010, 18 an alternate Mediterranean diet score, 18 Dietary Approaches to Stop Hypertension [DASH], 18 a high-dairy and high-fruit-and-vegetable and low-alcohol pattern score, 19 and vegetable-fruit-soy pattern 20 ), food groups (i.e., higher intakes of milk, 21 , 22 red meat, 23 , 24 , 25 vegetables, 26 , 27 and fruits, 26 , 28 as well as lower consumption of grilled meat, 29 high-cholesterol foods, 29 and processed meat intake 30 ), some nutrients (i.e., lower sodium, 31 , 32 and saturated fat 33 ); and 4) a higher risk of COPD was associated with lower fish intake 34 and in those with a smoking history. 35 Please see more results in Supplementary Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“…The DASH diet, Mediterranean dietary pattern, and vegetable and whole grain dietary pattern lower the risk of NCDs. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 Moreover, increased whole grain intake was associated with decreased NCDs, but the intake of such nutritious foods in the Western Pacific region is decreasing. 75 While the availability and access to low-priced, ultra-processed, and energy-dense foods, including refined grains, are increasing as the result of rapid industrialization and globalization as well as national policies and standards that have prioritized safety over nutritional values and health promotion.…”
Section: Recommendations For Future Actionsmentioning
confidence: 99%
“…However, these results have been inconsistent. Several meta-analyses and cohort studies have shown a negative correlation between fruits intake and the risk of diabetes mellitus [27][28][29] , whereas two studies conducted in European populations did not nd a correlation 30,31 . In our study, blood glucose levels were found to be one of the mediating effects between the 'nuts and fruits' dietary pattern and DKD.…”
Section: Discussionmentioning
confidence: 99%
“…For those with diabetes, foods with a low glycemic index, such as whole grains, non-starchy vegetables, legumes, and nuts, are best because they barely affect blood sugar levels (Forouhi et al, 2018). Studies have indicated that consumption of fresh or whole fruits was associated with a decreased risk of HbA1c among patients with diabetes (Du H et al, 2017;Li et al, 2023;Yu et al, 2022) substantial uncertainties remain about its potential effects on incident diabetes and, among those with diabetes, the risks of death and vascular complications. We aimed to assess the associations of fresh fruit consumption with the risk of incident diabetes and diabetic vascular complication.…”
Section: Discussionmentioning
confidence: 99%